Analisis Numerik 1D Pengendalian Banjir pada Wilayah Padat Penduduk dengan Persamaan St. Venant - Dian Indrawati Subagyo; Mohammad Bagus Adityawan; Muhammad Rizki Purnama; Rono Hadinagoro (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2020)
As one of the densest populations in Bandung City, Ujung Berung District has suffered because of flood disaster, which resulted several problems in that area. These problems arose due to non-optimal land handling, especially about a sporadic land alteration from agricultural to residential areas on the upstream. One of the disastrous area is the northern Ujung Berung at Griya Winaya Resident. The drainage channel on this resident was originally an irrigation channel system which been changed without an appropriate technical justification. Therefore, the residents, with Â±800 population or 300 household/Ha, struggled to deal with flood problems when they get rainfalls with an intensity more than 30 mm/hour. This research conducted at RT 05 RW 12 as the worst affected area, and used Storm Water Management Model (SWMM) software to determine flood routing by 1D St. Venant equation. Using a rainfall data from Cibiru rainfall station for 2005-2016 periods, the model successfully developed flood simulation at dense area with a narrow and winding channel. Moreover, the 10 (ten) years return period of annual flood can be managed with the increasing of drainage channel until 100 percent in dimension.